1996
DOI: 10.1086/310394
|View full text |Cite
|
Sign up to set email alerts
|

Are Hubble Deep Field Galaxy Counts Whole Numbers?

Abstract: We compute the two-point angular correlation function and number-magnitude relation of Hubble Deep Field sources in order to assess their nature. We find that the correlation peaks between 0.25 arcsec and 0.4 arcsec with amplitude of 2 or greater, and much more for the smallest objects. This angular scale corresponds to physical scales of order 1 kpc for redshifts z > 1. The correlation must therefore derive from objects with subgalaxian separations. At faint magnitudes, the counts satisfy the relation Number … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 10 publications
5
55
0
Order By: Relevance
“…), and be counted as several distinct faint sources. As suggested by Colley et al (1996) in this case strong correlations between sources on scales < 10 kpc should be found. A good test is therefore the two-point angular correlation function.…”
Section: Completeness Correctionsupporting
confidence: 67%
See 2 more Smart Citations
“…), and be counted as several distinct faint sources. As suggested by Colley et al (1996) in this case strong correlations between sources on scales < 10 kpc should be found. A good test is therefore the two-point angular correlation function.…”
Section: Completeness Correctionsupporting
confidence: 67%
“…Our best fit gives γ U = 0.47 ± 0.05, γ B ∼ 0.35 ± 0.02, γ V ∼ 0.28 ± 0.01 and γ I ∼ 0.28 ± 0.01 (see Volonteri et al 2000, for a detailed discussion). Colley et al (1996) suggested that galaxies in the HDF-N may suffer from a wrong selection. High redshift galaxies on optical images have a clumpy appearance: first the redshift moves the ultraviolet rest-frame light into the optical, so galaxies are observed in UV rest-frame where starforming regions are more prominent, second the fraction Table 4.…”
Section: Completeness Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulation continues until we obtain 10,000 '' sky pixels.'' Since faint galaxies are weakly clustered on small projected scales (Colley et al 1996(Colley et al , 1997Roche et al 1993), we have simply placed galaxies randomly in this simulation. For the surface density of galaxies as a function of apparent magnitude, we have adopted the HDF galaxy counts at V > 23 AB mag, which go 1.5 mag fainter than our own data (see Fig.…”
Section: Appendix B Flux From the Low Surface Brightness Wings Of Detmentioning
confidence: 99%
“…-These statistics are hard to measure at small radii, particularly when galactic components (such as giant HII regions) become difficult to distinguish from merging companions. This is often the case when probing distant galaxies in the rest-frame ultraviolet, ego in the Hubble Deep Field, where knots of star-formation cannot easily be distinguished from companions (Colley et al 1996). Not really measuring merger rate (see below).…”
mentioning
confidence: 99%